2023
DOI: 10.3390/ijms24076078
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Intra-Articular Injection, Physical Therapy, and Combined Treatments on Pain, Function, and Sarcopenia Indices in Knee Osteoarthritis: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Knee osteoarthritis (KOA) is associated with a high risk of sarcopenia. Both intra-articular injections (IAIs) and physical therapy (PT) exert benefits in KOA. This network meta-analysis (NMA) study aimed to identify comparative efficacy among the combined treatments (IAI+PT) in patients with KOA. Seven electronic databases were systematically searched from inception until January 2023 for randomized controlled trials (RCTs) reporting the effects of IAI+PT vs. IAI or PT alone in patients with KOA. All RCTs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…However, the findings could not be generalized because only soccer athletes with early osteoarthritis were included ( 17 ). Liao et al ( 18 ) performed a network meta-analysis to investigate the efficacy of the combination of injection therapies and physical therapies. The results supported the use of MSC, dextrose, PRP, PRGF, and botulinum toxin A in combination with physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings could not be generalized because only soccer athletes with early osteoarthritis were included ( 17 ). Liao et al ( 18 ) performed a network meta-analysis to investigate the efficacy of the combination of injection therapies and physical therapies. The results supported the use of MSC, dextrose, PRP, PRGF, and botulinum toxin A in combination with physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Their specific emphasis was on assessing the combined therapy's influence on pain levels, overall functional improvement, and walking capacity. Through this approach, they aimed to establish the most effective treatment option by ranking the effectiveness of each combined therapy regimen and exploring any factors that might influence treatment outcomes [77].…”
Section: Ha-based Therapy In Osteoarthritis Treatmentmentioning
confidence: 99%
“…In the specific case of the combination of intra-articular injections of HA and physical therapy, it was observed that this treatment appeared to be more effective in reducing pain compared with physical therapy alone. Additionally, it allowed for better walking capacity in the short term, both compared with physical therapy alone and in comparison with other intra-articular injections [77].…”
Section: Ha-based Therapy In Osteoarthritis Treatmentmentioning
confidence: 99%
“… 6 , 7 Treatment options for KOA range from non‐surgical interventions in the early stages to surgical treatments in advanced stages. 8 , 9 Most patients requiring surgery have medial compartment KOA, with high tibial osteotomy (HTO) and unicompartmental knee arthroplasty (UKA) as common surgical options. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Treatment options for KOA range from non-surgical interventions in the early stages to surgical treatments in advanced stages. 8,9 Most patients requiring surgery have medial compartment KOA, with high tibial osteotomy (HTO) and unicompartmental knee arthroplasty (UKA) as common surgical options. [10][11][12] HTO corrects joint deformities and abnormal force lines in the knee by shifting the load-bearing axis from the damaged medial compartment to the undamaged lateral compartment, thereby relieving pain.…”
Section: Introductionmentioning
confidence: 99%